Aspects of Protein Synthesis in vitro in Halobracterium cutirubrum - White, Bradley N. (My University, 1970)
This thesis proposed to investigate protein synthesis in extreme halophile, Halobaterium cutirubrum, especically in relation to the effect a high salt environment has on codon-anticodon recognitions. Many codon assignments were made on the basis of amino acid incorporation directed by random copolyribonucleotides in an in vitro protein synthesizing system. Detailed comparison was made of halophileic and E. coli tRNA in high and low salt assay systems. A study was also made of the mechanisms of the initiation of protein synthesis in this bacterium/
Title: Aspects of Protein Synthesis in vitro in Halobracterium cutirubrum, Author: Bradley N. White, Location: Thode